Operational Risk Mitigation Strategy in the Engineering Department : A Case Study of PT XYZ - Salisyah Salsabilah; Nur Rahmawati (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
Operational risk is one of the significant challenges that can hinder the achievement of a company's goals, especially in strategic departments such as the Engineering Department. Risk identification and mitigation are important steps to ensure smooth operations and maintain the company's overall productivity and performance. This study aims to evaluate and optimize operational risk mitigation strategies in the Engineering Department of PT XYZ, which operates in the cement production sector. With a qualitative approach, this study analyzes various risks faced, including design suitability, reliability of safety monitoring, and budget management. The results show that the implementation of systematic and proactive mitigation strategies can significantly reduce potential risks that can interfere with smooth operations. In addition, this study found that effective communication with stakeholders and the implementation of feedback from customers are essential to increase customer satisfaction and trust. The resulting recommendations include the preparation of project completion time standards, periodic evaluations of performance, and more detailed mapping of budget needs. Thus, this research contributes to the development of best practices that can be adopted by other companies in the same industry. The results of this study are expected to improve PT XYZ's operational performance and strengthen its position in a competitive market.